Unfolded protein response gene GADD34 is overexpressed in rheumatoid arthritis and related to the presence of circulating anti-citrullinated protein antibodies. (2nd April 2016) - Clavarino, Giovanna; Adriouach, Souad; Quesada, Jean-Louis; Clay, Marine; Chevreau, Maxime; Trocmé, Candice; Grange, Laurent; Gaudin, Philippe; Gatti, Evelina; Pierre, Philippe; Cesbron, Jean-Yves; Dumestre-Pérard, Chantal
Abstract: Growth arrest and DNA damage-inducible gene 34 (GADD34) is an inducible cofactor of protein phosphatase 1, which has an important role in the unfolded protein response. GADD34 has been shown to be necessary for type I interferon and proinflammatory cytokine production in response to viral infection in murine models. We investigate the expression of GADD34 in rheumatoid arthritis (RA), in which proinflammatory cytokines have an important pathogenic role. The objective of this study was to evaluate the potential of GADD34 expression as a biomarker in RA patients. We report a case–control study on GADD34 gene expression in peripheral blood mononuclear cells of patients ( n = 75) with RA and age- and sex-matched healthy controls ( n = 25). The study was approved by the relevant local ethics committees. GADD34 gene expression level in peripheral blood mononuclear cells was measured by quantitative PCR and analyzed with Mann–Whitney test. The relation between GADD34 gene overexpression and clinical or biological characteristics was analyzed with univariate and multivariate analysis. GADD34 gene expression was significantly higher in RA patients compared with healthy controls ( p ≤ 0.001). Interestingly, GADD34 overexpression in PBMC of patients was related to the presence of circulating anti-citrullinated protein antibodies ( p = 0.030). Data of this study strengthen the evidence of an unfolded protein response during the course of RA and provide an insight of the potential interest in GADD34 as a relevant marker for RA.